Investigation of Relationship Between Chemical Stress Factors and Certain Metabolites Including Cardenolides in Callus Cultures of Endemic Turkish Digitalis L. Species - Gunce Sahin; Sandeep Kumar Verma; Ekrem Gurel (International Journal of Secondary Metabolite)
The aim of the present research is to obtain relationship between different stress treatments [Cu (copper) and Hg (mercury)] and content of cardiac glycosides (digoxigenin, gitoxigenin, lanatoside C, digoxin and digitoxin) as secondary metabolites of commercial value for the pharmaceutical industry and to determine the antioxidant metabolites against stress conditions in callus cultures of endemic Turkish Digitalis species. The effects of different stress treatments on cardiotonic glycoside accumulation in D. lamarckii Ivanina, D. trojana Ivanina, D. davisiana Heywood and D. cariensis Boiss. ex Jaub. et Spach were investigated using HPLC. HPLC analysis revealed that all stress conditions were significantly effective at 5% significance level according to their control groups. The predominant cardiac glycoside was lanatoside C (Lan C) followed by digitoxin, digoxigenin, gitoxigenin and digoxin. No digoxin was detected in all treatments as well as in control groups. For the calibration curves, concentrations of 5, 10, 20, 30 and 40 mg/l digoxigenin, gitoxigenin, lanatoside C, digoxin and digitoxin were used (R2= 0.99). Cardenolides were eluted with acetonitrile (A) and water (B) gradients as follows: 0 to 20 min 20% (A), 80% (B); 20 to 23.40 min 30% (A), 70% (B); 23.40 to 30 min 25% (A), 75% (B) and 30 to 40 min 40% (A), 60%(B). Average peak area of the glycoside in samples was automatically calculated and monitored by ChemStation LC/MS software against that of standards. Enhanced production of cardenolides was achieved from callus cultures elicited with 50 μm CuSO4 and HgCl2. Higher amounts of cardenolides were obtained when callus of four Digitalis species were elicited with CuSO4. Results demonstrated that catalase (CAT, EC 1.11.1.6), superoxide dismutase (SOD, EC 1.15.1.1) activities, the total contents of phenolics and proline were markedly stimulated under stress conditions. All these results indicated that treatments have induced changes in the redox state of callus cells and suggest that this alteration change cardenolides accumulation and antioxidative status in Digitalis L. callus cultures.